2011
DOI: 10.3109/17435390.2011.552811
|View full text |Cite
|
Sign up to set email alerts
|

Size and surface charge of gold nanoparticles determine absorption across intestinal barriers and accumulation in secondary target organs after oral administration

Abstract: It is of urgent need to identify the exact physico-chemical characteristics which allow maximum uptake and accumulation in secondary target organs of nanoparticulate drug delivery systems after oral ingestion. We administered radiolabelled gold nanoparticles in different sizes (1.4-200 nm) with negative surface charge and 2.8 nm nanoparticles with opposite surface charges by intra-oesophageal instillation into healthy adult female rats. The quantitative amount of the particles in organs, tissues and excrements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
248
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(259 citation statements)
references
References 49 publications
9
248
0
2
Order By: Relevance
“…injection in rat [6,7] and mouse [8][9][10]. The bioavailability of orally administered AuNPs has also been studied in these animal models [10][11][12]. These studies have shown that size is one of the major determinants of biodistribution [7,9,13].…”
Section: Introductionmentioning
confidence: 99%
“…injection in rat [6,7] and mouse [8][9][10]. The bioavailability of orally administered AuNPs has also been studied in these animal models [10][11][12]. These studies have shown that size is one of the major determinants of biodistribution [7,9,13].…”
Section: Introductionmentioning
confidence: 99%
“…Biomolecules that are not replaced would serve as a corona 'memory' of the nanoparticle's previous environment. Therefore the corona composition could potentially depend not only on the current environment of the nanoparticle, but on all environments it has moved through 26,27 . Figure 2 illustrates this concept for inhaled nanoparticles carrying typical lung surfactant proteins, and other membrane components, when they reach the blood circulation 28,29 .…”
mentioning
confidence: 99%
“…Therefore, it is important to elucidate the uptake pattern of the polyester NPs, particularly in hepatic cell lines, as it is well established that the liver is a site of accumulation for many nanoparticles following exposure via various routes (e.g. intravenous injection, ingestion, inhalation/intratracheal instillation) [34,35,37]. The uptake of coated and uncoated P02 NPs in C3A cells suggested that the NPs were taken up by the cells in a time and concentration dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocytes were selected as the liver is the primary site of nanoparticle accumulation following exposure via different routes (e.g. intratracheal instillation, ingestion, intravenous injection), and existing evidence suggests that C3A cells respond similarly to primary human hepatocytes [34][35][36][37]. The internalization of coated and uncoated polymer nanoparticles by hepatocytes was assessed over time, and their effects on cell viability evaluated using three assays; Alamar Blue, Neutral Red, and 5-CFDA-AM [5-carboxyfluorescein diacetate, acetoxymethyl ester] CFDA-AM.…”
Section: Introductionmentioning
confidence: 99%